Characterisation of a well-type NaI(Tl) detector by means of a Monte Carlo simulation for radionuclide metrology application. (October 2021) - Heranudin,; Smith, M.L.; van Wyngaardt, W.M.; Guatelli, S.; Li, E.; Rosenfeld, A.
Abstract: A well-type NaI(Tl) detector was modelled and characterised by means of a Monte Carlo simulation, as part of a project to develop a 4πβ (Plastic Scintillator)-4πγ instrument to be used for the primary standardisation of radionuclides at ANSTO. The simulation based on GEANT4 was used to characterise the 4πγ detector in terms of potential dead layer/inactive materials, full energy peak efficiency, coincidence-summing correction, and energy resolution. An excellent agreement was obtained between the simulation results and the experimental measurements. Highlights: The Monte Carlo GEANT4 of the well-type NaI(Tl) was validated against measurements. Modelling of the dead layer has a significant effect on the low energy γ-ray. The GEANT4 simulation implements correction of coincidence-summing effects. Agreement of energy resolution between the modelled and the experimental spectra.